2020
DOI: 10.1371/journal.pmed.1003358
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 antibodies in people with an acute loss in their sense of smell and/or taste in a community-based population in London, UK: An observational cohort study

Abstract: Background Loss of smell and taste are commonly reported symptoms associated with coronavirus disease 2019 (COVID-19); however, the seroprevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies in people with acute loss of smell and/or taste is unknown. The study aimed to determine the seroprevalence of SARS-CoV-2 antibodies in a community-based population with acute loss of smell and/or taste and to compare the frequency of COVID-19 associated symptoms in participants with and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
61
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 24 publications
10
61
0
4
Order By: Relevance
“…Overall, Covid-19 among our HCWs was in most cases not found severe: one (1/36; 2.8%) was hospitalized (ICU). According with many other studies [ 16 , 17 , 19 , 35 , [38] , [39] , [40] ], in our data anosmia (complete among CoV(+) versus CoV(−) 55.6% versus 0.6%; partial 8.3% versus 6.5%) and ageusia (complete 38.9% versus 0.2%; partial 33.3% versus 6.0%) were strongly associated with CoV(+). The proportion of CoV(+) HCWs with olfactory and/or taste disorders varies greatly between studies: in an investigation by Lan et al 15.7% of the PCR-positive [ 41 ] and Lindahl et al 12.0% of the seropositive [ 17 ] show olfactory/taste disorders, whereas Villareal et al and Lombardi et al present considerably higher rates ranging from 70.0 to 76.9% [ 35 , 40 ] that accord with our data, where the respective figure is 77.1% for olfactory or taste disorders.…”
Section: Discussionsupporting
confidence: 85%
“…Overall, Covid-19 among our HCWs was in most cases not found severe: one (1/36; 2.8%) was hospitalized (ICU). According with many other studies [ 16 , 17 , 19 , 35 , [38] , [39] , [40] ], in our data anosmia (complete among CoV(+) versus CoV(−) 55.6% versus 0.6%; partial 8.3% versus 6.5%) and ageusia (complete 38.9% versus 0.2%; partial 33.3% versus 6.0%) were strongly associated with CoV(+). The proportion of CoV(+) HCWs with olfactory and/or taste disorders varies greatly between studies: in an investigation by Lan et al 15.7% of the PCR-positive [ 41 ] and Lindahl et al 12.0% of the seropositive [ 17 ] show olfactory/taste disorders, whereas Villareal et al and Lombardi et al present considerably higher rates ranging from 70.0 to 76.9% [ 35 , 40 ] that accord with our data, where the respective figure is 77.1% for olfactory or taste disorders.…”
Section: Discussionsupporting
confidence: 85%
“…[ 22 ] A study of individuals in London, UK with a loss of smell and/or taste found that antibody prevalence was even higher (78%) if testing was solely focused on anosmia/ageusia, which underscores the specificity of this symptom for SARS-CoV-2 infection despite methodological differences between these studies. [ 31 ] Our results align with other major studies and suggest that across geographies, a large proportion of infections occur with few or no symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…28 Change/loss of smell independently predicted seroconversion among HCWs in this study at follow-up and seropositivity at baseline. Similarly, recent loss of smell was associated with a three-fold increase in the risk of seropositivity for SARS-CoV-2 in a community-based cohort in the UK ( Makaronidis et al, 2020 ). Also, a meta-analysis reported that olfactory dysfunctions were found in 41% of 8438 COVID-19 patients from 13 countries ( Agyeman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%